2020
DOI: 10.3389/fneur.2020.542493
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of 3D T1-SPACE in Combination With 3D-TOF MRA for Follow-Up Evaluation of Intracranial Aneurysms Treated With Pipeline Embolization Devices

Abstract: Object: Follow-up evaluation of intracranial aneurysms treated by flow-diverting stents using MRI is challenging due to the presence of imaging artifacts. This study evaluated 3D T1-SPACE in combination with 3D-TOF sequence for follow-up evaluation of intracranial aneurysms treated with Pipeline embolization devices.Methods: Forty patients with 53 intracranial aneurysms who were treated with Pipeline Embolization Devices from October 2018 to July 2019 were enrolled in this study. All patients were evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…This result was consistent with findings from a previous study demonstrating that 3D T1-weighted SPACE was more accurate than TOF-MRA in the assessment of patency of the stented artery in 53 intracranial aneurysms treated with the Pipeline. 13 In this study, regardless of whether the simplified 2-grade or 3-grade scale was used, the HR-VW-MR imaging had a 100% coincidence rate with DSA in the evaluation of the patency of the parent artery. Therefore, HR-VW-MR imaging is a good technique for assessing the patency of the parent artery in intracranial VBDAs treated with reconstructive EVT.…”
Section: Patency Of the Parent Arterymentioning
confidence: 80%
“…This result was consistent with findings from a previous study demonstrating that 3D T1-weighted SPACE was more accurate than TOF-MRA in the assessment of patency of the stented artery in 53 intracranial aneurysms treated with the Pipeline. 13 In this study, regardless of whether the simplified 2-grade or 3-grade scale was used, the HR-VW-MR imaging had a 100% coincidence rate with DSA in the evaluation of the patency of the parent artery. Therefore, HR-VW-MR imaging is a good technique for assessing the patency of the parent artery in intracranial VBDAs treated with reconstructive EVT.…”
Section: Patency Of the Parent Arterymentioning
confidence: 80%
“…5,7 However, in the follow-up of intracranial stent-assisted coil embolization or flow diverter treated aneurysms, only few studies have so far analyzed the role of MR-VWI in evaluating instent patency. [8][9][10] In detail, in a prior study which evaluated stent-assisted coil embolization of intracranial aneurysms, MR-VWI was helpful in the identification of the 3 stenosis cases, providing similar results of DSA. 8 However, in this study, only baseline pre-contrast MR-VWI was performed, thus not allowing the possibility to evaluate vessel wall inflammatory changes.…”
Section: Discussionmentioning
confidence: 97%
“…An additional study, which analyzed intracranial aneurysms treated by FDS, compared MR-VWI performed with a 3D T1-SPACE sequence and TOF-MRA, demonstrating that MR-VWI provides better image quality and greater accuracy for evaluating stented parent arteries compared to TOF-MRA; all in-stent stenosis observed (5/46) were confirmed by DSA. 9 In a more recent study where a high-resolution MR-VWI sequence (scanning time: 11-13min) was performed in patients with intracranial aneurysms treated with FDS, focal mural enhancement of the parent vessel was commonly found in about 89% of patients. This observation suggests that focal mural enhancement can be considered an expected phenomenon in flow diverter therapy, related to reactive vessel wall inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a review of our own institutional follow-up routine showed that follow-up examinations of patients treated with FDS are rarely performed by DSA after more than 2 years but are usually performed by MRI. This might contribute to a low rate of detection since MRI with standard sequences has reduced specificity for stenosis in arterial segments treated by FDS [5].…”
Section: Discussionmentioning
confidence: 99%